TEACHING NARRATIVE TEXT IN READING COMPREHENSION BY USING DECISION MAKING TO THE EIGHTH GRADE STUDENTS OF FITRA ABDI JUNIOR HIGH SCHOOL OF PALEMBANG - ANA THEREANA (ELTE Journal (English Languange Teaching and Education), 2016)
ABSTRACTThe problem of this study was”is it effective to teach reading narrative text in reading comprehension by using decision making to the eighth grade students of Fitra Abdi junior high school of Palembang?.”The main objective of this study was to find out whether or not it is effective to use decision making reading in teaching reading narrative text.      This study was done through the pre-experimental method. The population of this study was 60 eighth grade students with 30 students as the sample which was chosen though cluster rendom sampling. The technique for collecting the data was a written test, pre-test and post-test. The data were analyzed through the formula of matched t-test. The result of this study indicated that after teaching narrative text in reading comprehension by using decision making,the students mastery of reading comprehension improved. Their everage level increased from the (6.11) to the (6.95). it was supported by the result of the data analysis that showed the t-obtained 6.461 which exceeded 1.671 as the critical value. It mean that the Ho was rejected, and Ha was accepted. It could be concluded that it was effective to teach narrative text in reading comprehension to the eighth grade students of Fitra Abdi junior high school of Palembang. Keywords: teaching, narrative text, decision making